A COMPARATIVE STUDY OF THE EFFECT OF ACETYLCHOLINE AND PROSTAGLANDIN F2a ON ISOLATED TRACHEALIS MUSCLE OF GUINEA *PIG - Nawaz, Shah.; Kamran, MAJ.; Ahmad, Qazi Rashid; Rashid, Abdul (Journal of Ayub Medical College Abbottabad, 1990)
Abstract: Acetylcholine and prostaglandin F2a, both produce constriction of the broncheal smooth muscle. In present study, the bronchoconstricting effect of both these drugs was compared by utilizing the isolated trachea of guinea-pig as experimental tissue. Results of the present study have shown that acetylcholine produces more powerful constriction of the isolated trachea of the guinea-pig. At high concentrations, the effect of acetylcholine was more poten than that of prostaglandin F2a. But in low concentrations, the bronchoconstricting effect of both the drugs was almost similar.